Synthesis of curcumin‐loaded shellac nanoparticles via co‐precipitation in a rotating packed bed for food engineering. Issue 26 (13th April 2022) - Zou, Yuanzuo; Wang, Fen; Li, Angran; Wang, Jie‐Xin; Wang, Dan; Chen, Jian‐Feng
Abstract: Practical application of versatile nanomaterials to food engineering is desirable. In this study, highly encapsulated curcumin‐loaded shellac (Cur@Lac) nanoparticles are efficiently prepared via a rotating packed bed (RPB). In this modified co‐precipitation process, the morphology of Cur@Lac nanoparticles is systematically investigated under experimental parameters involving the high‐gravity level, the volume of antisolvent and the concentration of shellac. By virtue of the highly structured polymeric ester matrices of shellac and adequate supersaturation brought from RPB on a microscale, the obtained Cur@Lac nanoparticles with uniform size exhibit high encapsulation efficiency of over 96%. After 2 months of storage at room temperature, the aqueous Cur@Lac nanodispersions exhibit long‐term stability with no agglomeration or sedimentation, and the final retention rate of curcumin was over 85%. Colored drinks of fruit syrup (pH = 4.0), fruit soda (pH = 6.0), and soda water (pH = 8.3) are prepared by using the Cur@Lac as the colorant, which possessed orange‐yellow color. The nanocomposites of alkali‐sensitive indicators based on cellulose paper and gelatin film demonstrated in the work show promising application value for sensing of alkaline solution and gas of perishable food. Abstract : Curcumin‐loaded shellac nanoparticles are successfully prepared by modified co‐precipitation method in a rotating packed bed. As the amphipathic matrix, biopolymer (shellac) encapsulates a sensitive multifunctional material (curcumin) with high encapsulation efficiency and stability. The composite nanoparticles can be used as natural colorants dispersed in daily drinks and applied for sensing of alkaline solution and gas of perishable food.